WORKING WITH GIFTED CHILDREN IN CHINA: SCIENTIFIC EXPLORATION AND THEORETICAL AND METHODOLOGICAL APPROACHES - Stanislav S. Naumenko (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
Today in China there are two main philosophical positions on the education and upbringing of gifted and talented people: one position emphasizes the importance of natural abilities and talents, the other - emphasizes the idea that the talent of every child can be brought up and developed. Although gifted children education in China has been evolving for more than three decades, there is still no law governing working with them. Special programs for gifted children exist in only a few schools in economically developed areas. China does not have a clear national and regional policy to support education for the gifted. On the basis of psychological research and educational practice, a procedure and methodology for identifying and selecting gifted children has been developed, which is based on several key aspects: priority is given to high academic performance, general intellectual abilities, personal qualities, level of motivation, creativity. The curriculum for gifted students is usually formed on the approach of «accelerated learning», which involves mastering the content of learning in a shorter period of time, compared to the traditional program. Gifted children graduate four to five years earlier. Several educational institutions offer «enrichment» programs, which provide in-depth study of individual subjects in accordance with the abilities and needs of a child. China is actively conducting research in the field of giftedness and talent, which involves the implementation of two approaches: a psychological approach that supports the natural development of children; an educational approach that takes into account the special needs of gifted students and offers them appropriate educational programs and services. Most research is based on a psychological approach, so in educational practice there are not enough illustrations to formulate the results of programs for the development of gifted and talented people. It is very important for Chinese scientists to identify and solve practical problems that usually arise in China. The psychological and pedagogical theory of teaching and upbringing of gifted children is actively developing, which, taking into account Confucian traditions, emphasizes the role of personal efforts and social influence in achieving academic success. The implementation of talent development programs for overall academic achievement has shown high performance by Chinese students in several international competency assessments, such as PISA and TIMMS, and many graduates have excelled in academic, technical and professional fields, both in China and abroad